PROGRESS OF KHYBER PAKHTUNKHWA (PAKISTAN) TOWARDS UNIVERSAL HEALTH COVERAGE - Ayub, Ayaz; Khan, Raheel Shahab; Khan, Sheeraz Ahmad; Hussain, Hamid; Tabassum, Afshan; Shehzad, Jawad Ahmed; Shah, Syeda Sonia (Journal of Ayub Medical College Abbottabad, 2018)
Background: Khyber Pakhtunkhwa (KP) launched its flagship Social health protection initiative (SHPI), named Sehat Sahulat Program (SSP). SSP envisions to improve access to healthcare for poorest of the poor and contribute towards achieving Universal Health Coverage (UHC). Current study was undertaken to analyze SSP in context of UHC framework i.e. to see as to (i) who is covered, (ii) what services are covered, and (iii) what extent of financial protection is conferred. Methods: We conducted thorough archival research. Official documents studied were concept paper(s), approved planning commission documents (PC-1 forms) and signed agreement(s) between government of KP and the insurance firm. Results: SSP enrolled poorest 51% of province’ population i.e. 14.4 million people. It covers for all secondary and limited tertiary services. Maximum expenditure limit per family per year is Rs.540, 000/-. Government pays a premium of Rs.1549/- per year per household to 3rd party (insurance firm) which ensures services through a mix of public-private providers. Conclusion: The breadth, depth and height of SSP are significant. It is a phenomenal progress towards achieving UHC. Keywords: Universal Health coverage; healthcare financing; Health insurance; social health protection.